Literasi Digital dalam Penerimaan Berita Hoaks Tentang Lowongan Pekerjaan Melalui Telegram - Pratamaputra, Geovany Friawan; Riesta Ayu Oktarina (LPPM Stikosa-AWS, 2024)
Residents need information about job vacancies in order to get a job easily. Before the development of innovation, job vacancy information provided to citizens was usually only through print media. But as technology develops very rapidly, it makes it easier to spread data on job openings. One of the digital media used to find information about job vacancies is telegram. In the telegram there is still a lot of information that is false and untrue. In the amount of information about job vacancies circulating on telegram. The author found 3 factors, disinformation, misinformation and malinformation. The interviewees felt that these terms were still too technical and complicated to be used for the wider community, whose level of understanding and literacy was still low. Public understanding of the dissemination of information in telegram media is not good enough and is less critical. However, some people already know the importance of digital literacy to filter information well and not easily provoked by the news circulating.